STUDY OF UNFAVORABLE ENVIRONMENTAL CONDITIONS FACTORS AFFECTING THE IMMUNE SYSTEM (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article deals with the study of the influence of inconvenient ecological conditions on the immune system of some mammals. The important directions of Immunobiology are analyzed. An important direction in immunobiology is the study of the influence of chemical and physical factors on the immune system of the body, normal functioning, which provides homeostasis of the internal environment of the body. The immune system is very sensitive to various adverse environmental factors. Particular attention is paid to the physical, chemical factors of the environment, which can lead to negative processes in the body of experimental rats